AB0134 Role of Macrophages in the Cardiovascular Disease Associated to Rheumatoid Arthritis: Effects of Anti-CCPS in the Phenotypic Switching and the Insulin Signalling. (9th June 2015) - Ruiz-Limon, P.; Jimenez-Gomez, Y.; Perez-Sanchez, C.; Abalos-Aguilera, M.C.; Aguirre, M.A.; Calvo, J.; Ortega, R.; Collantes-Estevez, E.; Escudero, A.; Lopez-Pedrera, C.; Barbarroja, N.
Abstract : Background: Macrophages play a key role in the pathogenesis of the rheumatoid arthritis (RA). Under certain stimulus conditions these cells are able to switch their phenotypes to M1 or M2 states, which are characterized by different inflammatory and tissue repair properties. Thus, M1 macrophages are predominantly recruited in inflammatory states and associated with tisular damage. An imbalance in the M1/M2 proportion has been reported in the synovium of RA patients. The molecular mechanisms undertaken this phenotypic switching in RA are not completely defined. In addition, the role of anti-CCPs antibodies in the switch of macrophage polarization has not been studied yet. Objectives: To analyze the role of anti-CCPs in the polarization state, inflammatory process and the insulin signalling of macrophages Methods: M0 macrophages were differentiated from the monocytic cell line THP-1 and primary healthy monocytes. These macrophages were treated with different concentrations of IgGs isolated from healthy donors or RA patients having high levels of anti-CCPs and non-rheumatoid factor for 96 hours. Cells were collected each 24 hours of treatment. In order to analyze the response to insulin, the macrophages were treated with insulin (100 nM) for 10, 20 and 30 min before collecting the cells. The characterization of the polarization states M1 and M2 was performed through flow cytometry and the mRNA expression levels of M1 markers (HLA-DR, iNOS, IL1b, TNFa e IL-23) and M2 (CD206, Arg e IL-10). Moreover, the JNK expression and phosphorylation was analyzed. Finally, the response to insulin was studied through the mRNA expression of AKT and IRS-1 and the protein expression and phosphorylation of AKT (a key molecule mediating insulin signalling). Results: Flow cytometry studies showed that macrophages treated with IgGs anti-CCPs had higher protein expression of M1 markers such as HLA-DR and iNOS and reduced expression of CD206, M2 marker, compared with macrophages treated with IgGs isolated from healthy donors. In addition, IgGs anti-CCPs increased the mRNA expression levels of TNFa, IL1b and IL-23, molecules associated to M1 state, and reduced expression of IL-10, mainly expressed by M2 macrophages. After treatment with IgGs anti-CCPs, macrophages showed significantly lower AKT phosphorylation induced by insulin compared to the macrophages treated with normal IgGs. Moreover, anti-CCPs reduced the expression of AKT and IRS-1. This reduction was accompanied with an increase in the JNK phosphorylation, main molecule initiating the process of inflammation. These effects were significant after 24 hours treatment with 100 ug/ml doses of anti-CCPs. Conclusions: 1) Anti-CCPs antibodies act as inductors of M1 polarization state, promoting an imbalance of M1/M2 proportion which has been associated with a chronic inflammatory profile and joint damage in RA. 2) These antibodies also produce a defect in the insulin signalling of macrophages, by reducing the response to insulin, suggesting its possible implication in the insulin resistance and the development of the metabolic syndrome related to RA. Acknowledgements: Funded by: CTS7940, PI12/01511, PI2013-0191, SER Disclosure of Interest: None declared